Molecular Analysis of Microbial Diversity in Advanced Caries - Chhour, Kim-Ly (American Society for Microbiology (ASM), 2005)
Real-time PCR analysis of the total bacterial load in advanced carious lesions has shown that the total load exceeds the number of cultivable bacteria. This suggests that an unresolved complexity exists in bacteria associated with advanced caries. In this report, the profile of the microflora of carious dentine was explored by using DNA extracted from 10 lesions selected on the basis of comparable total microbial load and on the relative abundance of Prevotella spp. Using universal primers for the 16S rRNA gene, PCR amplicons were cloned, and approximately 100 transformants were processed for each lesion. Phylogenetic analysis of 942 edited sequences demonstrated the presence of 75 species or phylotypes in the 10 carious lesions. Up to 31 taxa were represented in each sample. A diverse array of lactobacilli were found to comprise 50% of the species, with prevotellae also abundant, comprising 15% of the species. Other taxa present in a number of lesions or occurring with high abundance included Selenomonas spp., Dialister spp., Fusobacterium nucleatum, Eubacterium spp., members of the Lachnospiraceae family, Olsenella spp., Bifidobacterium spp., Propionibacterium sp., and Pseudoramibacter alactolyticus. The mechanisms by which such diverse patterns of bacteria extend carious lesions, including the aspect of infection of the vital dental pulp, remain unclear.